Skill-relatedness and firm diversification - Frank Neffke; Martin Svensson Henning (Max Planck Institute of Economics, 2009)
The concept of relatedness between industries plays an increasingly central role in economics and strategic management. However, relatedness has remained rather elusive in empirical terms. In this article, we investigate relatedness between industries in terms of the extent to which the same human capital can be employed in different industries. In particular, we investigate the skill-relatedness among different industries by investigating labor flows between industries. The data used are Swedish employer linked data on individuals. Our statistical framework assesses the degree to which labor flows between pairs of industries are in excess of expected levels and use this as a quantification of Revealed Skill Relatedness. A network picture of 435 4-digit industries and the relatedness linkages between them shows that the relations among industries are far more complex than the industrial classification system suggests. Moreover, when investigating corporate diversification, we find that firms are far more likely to diversify into industries that are strongly skill-related to their core activities industries than into unrelated industries.
Keywords: 330